Pengaruh Asimetri Informasi dan Pengungkapan Sukarela terhadap Biaya Modal Ekuitas (Studi Empiris pada Perusahaan Manufaktur yang terdaftar Di Bursa Efek Indonesia Tahun 2015-2017) - Febrianingsih Putri; Erna Setiany (Jurnal Pena-Mas Akuntansi, 2020)
This study aims to examine and analyze the effect of information asymmetry and voluntary disclosure on the cost of equity capital. Within the context of this research, Asymmetry Information is measured using a relative bid-ask spread, Voluntary Disclosures are measured using a disclosure index. Meanwhile, the cost of equity capital is measured using the capital asset pricing model. Data analysis techniques are multiple regression techniques. The population in this study were 142 manufacturing companies listed on the Indonesia Stock Exchange (IDX) with a research period of 2015 to 2017. The samples used were 43 companies obtained by purposive sampling technique. The result of this research indicates that information asymmetry have influences significantly toward the cost of equity capital on listed companies from the manufacturing sector at the Indonesia Stock Exchange. While voluntary disclosure does not affect the cost of equity capital on listed companies from the manufacturing sector at the Indonesia Stock Exchange.